Implementasi Peraturan Walikota Denpasar Nomor 42 Tahun 2018 Tentang Tata Cara Pemotongan Pohon Perindang Dikota Denpasar - Ni Kadek Yuliantari; I Wayan Gde Wiryawan2 (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
The environment is a habitat that significantly influences the survival of living beings. From year to year, environmental problems continue to increase and tend to be uncontrollable. A common problem faced by major cities in Indonesia is the rapid growth of the population in urban areas. The history of environmental management in urban areas, particularly concerning shade trees, indicates that there have been policy changes over time. Data from the Denpasar City Environmental and Sanitation Agency indicate that over the past five years, there has been a significant increase in the number of public complaints regarding the illegal cutting of shade trees. The cutting of shade trees is often carried out carelessly without considering its ecological impact. Currently, although there have been Denpasar Mayor Regulation Number 42 of 2018, which regulates the procedures for cutting shade trees, Its implementation still faces various obstacles. Implementing a policy is not an easy matter, especially in achieving common goals